Design and synthesis of a hydrogen peroxide-responsive amino acid that induces peptide bond cleavage after exposure to hydrogen peroxide. Issue 28 (8th July 2015) - Kita, Miku; Yamamoto, Jun; Morisaki, Takuya; Komiya, Chiaki; Inokuma, Tsubasa; Miyamoto, Licht; Tsuchiya, Koichiro; Shigenaga, Akira; Otaka, Akira
Graphical abstract: Abstract: Oxidative stress-responsive compounds are attracting significant attention in the field of medicinal chemistry and chemical biology. Here, we disclose the development of a hydrogen peroxide (H2 O2 )-responsive amino acid that induces peptide bond cleavage in the presence of H2 O2 that closely relates to oxidative stress. The H2 O2 -responsive amino acid possessing a boronate or boronic acid moiety was incorporated into a peptide using Fmoc-based solid-phase peptide synthesis or that with minor modifications, respectively, and the peptide bond cleavage of the obtained peptide was successfully triggered by the addition of H2 O2 .